Penerapan Teknik Cognitive Restructuring untuk Mengurangi Kecemasan Siswa dalam Menghadapi Ujian Semester - Pradana, Sapta Rizki; Napisah, Siti; Mursidi, Agus (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2023)
The problem in this study is anxiety in the face of demanding semester exams, which can be detrimental to students because it will make them stressed and interfere with their ability to learn. So, in order to provide important services to children and minimize the level of anxiety, a cognitive restructuring approach is used. The aim of this study was to ascertain whether using a cognitive restructuring approach to reduce exam-related anxiety is beneficial or not. Pretest-posttest design with one group is a research approach used in this pre-experimental study. students of Class X TKJ 2 SMK PGRI 1 Giri Bannyuwangi, consisting of 40 students, and 8 subjects selected from the exam with high and very high anxiety categories were sampled in the study. Purposive sampling is the sampling method used. The method of data collection is a questionnaire (Google form).Test the validity of the instrument using SPSS version 25. Based on the calculation results obtained tcount is 2.365 at degrees of freedom (df) 7, then compared to ttable is 12.568, then tcount > ttable, (12.568 > 2.365), with a sign 2 tailed value < of the value critical 0.005, ie 0.000 <0.005. So it can be concluded that H0 is rejected and Ha is accepted or it can be said that the use of cognitive restructuring techniques is effectively used to reduce student anxiety in facing final exams.